Non-invasive scalp recording of electroencephalograms and evoked potentials in unanesthetized horses using a 12-channel active electrode array - Itoh, Kosuke; Kikumura, Norihide; Maeda, Tamao; Hirata, Satoshi; Ringhofer, Monamie (Frontiers in Veterinary Science, 2024)
Despite the long history of the horse-human bond, our understanding of the brain and mind of horses remains limited due to the lack of methods to investigate their brain functions. This study introduces a novel methodology for completely non-invasive, multi-channel recording of electroencephalography (EEG) and evoked potentials in awake horses to examine equine auditory cortical processing. The new approach utilizes specially designed brush-shaped active electrodes that facilitate stable signal acquisition through the hair coat by penetrating electrode pins and integrated pre-amplifiers. A 12-channel electrode array provided greater scalp coverage than prior work. As a proof of concept, clear cortical auditory evoked potentials (CAEPs) were recorded in response to sound onsets and offsets. The equine CAEP waveform morphology resembled the human P1-N1-P2-N2 complex, although the latencies were shorter than typical human values. The CAEP amplitudes were maximal at centroparietal electrodes, contrasting with the frontocentral distribution seen in humans, potentially explained by differences in auditory cortex orientation between species. This non-invasive multi-electrode method enables the evaluation of cognitive abilities, normal and abnormal brain functions, and advances scientific understanding of the equine mind. It offers potential widespread applications for recording EEGs and evoked potentials in awake horses and other medium-to-large mammalian species.